Toronto’s Cartographic Birth Certificate: Hiding in Plain Sight for 350 Years - Laprairie, Rick (Ontario History, 2018)
This article posits that the earliest map to have ever used the name Toronto as a place is uncovered. Previously unnoticed, the name “Tarontos Lac,” for today’s Lake Simcoe, is on a 1678 map by Jean-Baptiste-Louis Franquelin. His map, “Carte pour servir a l’eclaircissement du Papier Terrier de la Nouvelle France,” is now recognized as Toronto’s cartographic birth certificate. The article describes the map, discusses how the discovery came about and why the name may have gone unnoticed until now. This cartographic study is set in the history of the exploration of the Great Lakes region and the Mississippi River. Three other unsigned and undated period maps, often claimed as “Toronto” firsts, are also examined. These claims are dismissed, as revised attributions show them to have been by different cartographers and dated later than originally thought, making Franquelin’s map the oldest. The cartographic genealogy of the name Toronto is traced back through three and a half centuries to its initial appearance on Franquelin’s map.